2016
DOI: 10.1016/j.copsyc.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Priming in economics

Abstract: Conceptual priming has become an increasingly popular tool in economics. Here, we review the literature that uses priming in incentivized experiments to study economic questions. We mainly focus on the role of social identity, culture, and norms in shaping preferences and behavior. We also discuss recently raised objections to priming research and conclude with promising avenues for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…These studies typically evaluate the priming intervention under stable conditions against a neutral control. Similar to comparing two conditions A and B in an experiment, as we do, this method circumvents many difficulties and identifies the causal impact of identity in heterogeneous social groups (for a discussion, see Cohn and Maréchal, 2016). The results of this literature suggest that there are important quantitative moderators of in-group bias.…”
Section: Further Literaturementioning
confidence: 89%
“…These studies typically evaluate the priming intervention under stable conditions against a neutral control. Similar to comparing two conditions A and B in an experiment, as we do, this method circumvents many difficulties and identifies the causal impact of identity in heterogeneous social groups (for a discussion, see Cohn and Maréchal, 2016). The results of this literature suggest that there are important quantitative moderators of in-group bias.…”
Section: Further Literaturementioning
confidence: 89%
“…Providing interviewers with a series of these questions, such as by asking them to TA B L E 4 Differences in candidate rating by intervention consider personal connections they feel with a candidate, or general stereotypes they may hold, could bring potential biases into awareness and limit their influence on interview evaluation. [43][44][45] The further structuring of interviews is a final way of potentially improving the integrity of the interview process. Research has suggested that structured interviews result in greater inter-rater reliability.…”
Section: Deference To Authority Figuresmentioning
confidence: 99%
“…Empirically identifying the causal impact of identity is difficult, first, because several forms of identity -gender, religion, caste and race, for example -cannot be randomly assigned, and second because ethical considerations dictate caution in broaching these potentially sensitive topics. As a result, several empirical studies employ an experimental psychology tool called 'priming' -the process of providing subtle mental cues -to make the relevant aspect of identity salient (Cohn and Maréchal 2016). Lab and field experiments using priming or other identification mechanisms have augmented theoretical models with evidence of the role of identity in shaping cognitive or educational outcomes (Afridi, Li, and Ren 2015;Hoff andPandey 2006, 2014), economic and social preferences (Benjamin, Choi, and Strickland 2010;Y.…”
Section: Identity and Information: The Literaturementioning
confidence: 99%